Reconceptualizing Local Wisdom Values in Regulations for Micro and Small Enterprises in Maluku to Support Local Economic Development - Ikhwansyah, Isis; Rahmawati, Ema; Hetharie, Yosia (PADJADJARAN JURNAL ILMU HUKUM (JOURNAL OF LAW), 2025)
This study seeks to examine and evaluate the efficacy of implementing the principle of "Bhinneka Tunggal Ika" (unity in diversity), which embodies local wisdom, in the governance of micro and small enterprises in Maluku Province as an aspect of local legal development. The principle of Bhinneka Tunggal Ika needs to be incorporated into laws and regulations, particularly regional legal mechanisms related to micro and small enterprises, in compliance with the Law on the Formation of Legislation. In Maluku's legal landscape, many regional legal products pertaining to micro and small enterprises fail to incorporate the principles of local wisdom into their content. This socio-legal investigation study integrates empirical legal research methods with doctrinal legal research. Primary and secondary data were gathered through interviews and literature reviews. The study results suggest that the legal protection provided to micro and small enterprise owners in Maluku has been ineffective. In addition, the legal content of regional legal products in Maluku fails to adequately account for value derived from local wisdom, as required by statutory provisions. Thus, it is necessary to reconsider incorporating values from local wisdom into various regional legal instruments related to developing and empowering micro and small enterprises in Maluku. This approach will support regional flagship products while facilitate the growth within the local economy, preserving the values of local wisdom in the face of global developments.